Change in Cav3.2 T-Type Calcium Channel Induced by Varicella-Zoster Virus Participates in the Maintenance of Herpetic Neuralgia - Li, Rongzhen; Ou, Mingxi; Yang, Shaomin; Huang, Jiabin; Chen, Jiamin; Xiong, Donglin; Xiao, Lizu; Wu, Songbin (Frontiers in Neurology, 2021)
Pain, as the most prevalent neurological complication of herpes zoster (HZ), may occur before or during the rash onset or even after the rash has recovered. Particularly, postherpetic neuralgia (PHN) is a refractory chronic condition, usually defined as pain persisting for 3 months or longer from the onset of HZ. Pain evoked by HZ impairs the normal physical and emotional functions of the patients, severely reducing their quality of life. However, how zoster-associated pain occurs and develops into PHN are elusive, making PHN difficult to predict. Uncovering the pathogenesis of zoster-associated pain (or HN) helps us to better understand the onset of PHN and supports developing more effective treatments. In this study, we successfully constructed a model for zoster-associated pain through varicella-zoster virus (VZV) infections of mouse footpads and pain behavior assessments. Next, we used the Kyoto Encyclopedia of Genes and Genomes (KEGG) and the Gene Ontology (GO) to analyze PHN rodent dorsal root ganglion (DRG) gene microarray data and found that calcium signal disorder might be involved in the onset of PHN. By using reverse transcription real-time fluorescent quantitative PCR (RT-qPCR) and Western blotting, we confirmed that VZV infection could significantly upregulate the expression of T-type calcium channel Cav3.2 in DRG and spinal dorsal horn (SDH). Intrathecal administration of Cav3.2 blocker (2R/S)-6-prenylnaringenin (6-PNG) relieved mechanical and thermal hyperalgesia induced by VZV. Taken together, our data indicated that VZV might participate in the occurrence and development of HN by upregulating the expression of Cav3.2 in DRG and SDH. These findings will help to reveal the underlying mechanisms on long-lasting pain and PHN formation, providing a new insight that Cav3.2 can be the promising drug target for remitting PHN.